Fabrication and Study of Nano catalysis for Alkaline Fuel Cell - . Ali, Nathera . A; Chied, Baha . T; Mohammed, Haleemah J. (Iraqi Journal of Science, 2019)
In this paper the manufacture of an alkaline fuel cell electrodes made upfrom a Nano mesh (Pt:NiO) catalyst has been studying , made from a Nano mesh (Pt:NiO ) catalyst. The general morphology of the samples is were imaged by using with the an Atomic Force Microscope (AFM) to determine the roughness of the prepared surface, it constructed from nanostructure with dimensions in order of 35 nm. The Structural characteristics were studied through the analysis of X-ray diffraction (XRD) of the prepared nanomaterial for determining the yielding phase;1. 72 volt was also obtained at 0.02 A/cm2 current density for an alkaline fuel cell.